To convert the quadratic \( y = 2(x - 5)^2 - 10 \) from vertex form to standard form, we need to expand the equation.
-
Start with the vertex form: \[ y = 2(x - 5)^2 - 10 \]
-
Expand \( (x - 5)^2 \): \[ (x - 5)^2 = x^2 - 10x + 25 \]
-
Substitute back into the equation: \[ y = 2(x^2 - 10x + 25) - 10 \]
-
Distribute the 2: \[ y = 2x^2 - 20x + 50 - 10 \]
-
Combine like terms: \[ y = 2x^2 - 20x + 40 \]
Now, we have the standard form of the quadratic: \[ y = 2x^2 - 20x + 40 \]
So, the standard form is: \[ y = 2x^2 + (-20)x + 40 \]
Thus, in the format requested, the answer is:
- The coefficient of \( x^2 \) is \( 2 \)
- The coefficient of \( x \) is \( -20 \)
- The constant term is \( 40 \)